A 12-week randomized controlled pilot study of dance exergaming in a group: Influence on psychosocial factors in adolescent girls - Amanda E. Staiano; Robbie A. Beyl; Daniel S. Hsia; Peter T. Katzmarzyk; Robert L. Newton Jr (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace, 2018)
Dance exergaming, which involves playing an interactive video game that requires the player to make upper and lower body movements by dancing to music, may provide a social physical activity experience that positively impacts psychosocial health. The objective of this randomized controlled study was to examine the effects of group-based dance exergaming on adolescent girls’ psychosocial health including enjoyment, subjective health, perceived peer support, and health-related quality of life. Forty-one adolescents with overweight/obesity were randomly assigned to a 12-week dance exergaming intervention or to a control group. Peer support, subjective health, and health-related quality of life (HRQOL) were assessed pre- and post-intervention, and intervention participants rated enjoyment after each exergaming session. Repeated measures analysis of covariance models controlling for age and baseline body mass index were used to examine condition differences. Results indicated that subjective health improved in the exergaming condition more than control (p = .02). Ratings of peer conflict after the intervention were significantly different by condition (p = .01), with peer conflict stabilizing in the exergaming group and worsening in the control group. There was no difference by condition for HRQOL. Enjoyment remained high throughout the intervention. In summary, group exergaming improved subjective health, stabilized peer conflict, and provided an enjoyable physical activity experience for overweight adolescent girls.